2011
DOI: 10.1186/1471-2458-11-s3-s28
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of oxygen systems for treatment of childhood pneumonia

Abstract: BackgroundOxygen therapy is recommended for all of the 1.5 – 2.7 million young children who consult health services with hypoxemic pneumonia each year, and the many more with other serious conditions. However, oxygen supplies are intermittent throughout the developing world. Although oxygen is well established as a treatment for hypoxemic pneumonia, quantitative evidence for its effect is lacking. This review aims to assess the utility of oxygen systems as a method for reducing childhood mortality from pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Antibiotics, appropriate monitoring of hypoxemia, and oxygen supplementation are fundamental in the treatment of pneumonia and associated complications.Oxygen supplementation is widely used in acute care settings around the world and is recommended by the World Health Organization (WHO) as supportive treatment for hypoxemia. 5,6 However, due to cost, implementation and logistical challenges, oxygen remains under-utilized or inaccessible in many low-to middle-income countries (LMICs). Additional barriers include lack of guidelines and training on oxygen use, access to affordable and accurate blood oxygen saturation monitoring devices and unreliable electrical supply.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics, appropriate monitoring of hypoxemia, and oxygen supplementation are fundamental in the treatment of pneumonia and associated complications.Oxygen supplementation is widely used in acute care settings around the world and is recommended by the World Health Organization (WHO) as supportive treatment for hypoxemia. 5,6 However, due to cost, implementation and logistical challenges, oxygen remains under-utilized or inaccessible in many low-to middle-income countries (LMICs). Additional barriers include lack of guidelines and training on oxygen use, access to affordable and accurate blood oxygen saturation monitoring devices and unreliable electrical supply.…”
mentioning
confidence: 99%
“…Oxygen saturation at admission and clinical diagnoses were not significantly different in fatal cases compared to nonfatal cases. The frequency of oxygen delivery interruptions was similar in fatal and nonfatal cases.Oxygen delivery interruptions in the fatal group were nearly three times longer than the recovered group (median: 28 minutes [IQR: 24-31] vs 10 minutes [IQR:[4][5][6][7][8][9][10][11][12], P = .072); however, these findings were not statistically significant at the α = .05 level of significance. Oxygen availability at 11 medical facilities in rural Kenya ET AL.…”
mentioning
confidence: 99%
“…The SaO 2 values recorded statistically significant increases both after 30 minutes and after 60 minutes from the initiation of oxygen therapy, both by simple face mask and nasal cannula. The specialized literature specifies the importance of initial evaluation and periodical reevaluation of SaO 2 in patients with acute respiratory failure caused by respiratory diseases by both SaO 2 and SpO 2 (Duke et al, 2009;Catto et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 590 health centers and hospitals across 22 low- and middle-income countries, only 42% reported that oxygen was always available for anesthetic care, whereas 35% had no source [8]. Another evaluation estimated that improving oxygen facilities could avert approximately 122,000 pediatric deaths from pneumonia per year [9]. The remaining facilities sometimes had oxygen available.…”
Section: Introductionmentioning
confidence: 99%